Pattern of Sexually Transmitted Infection in Tertiary Care Center of Eastern Nepal - Pradhan, Manish; Rai, Anjan; Karki, Sunita; KC, Srijana (Journal of Nobel Medical College, 2026)
Background: Sexually transmitted infections remain a major public health concern globally, particularly in low- and middle-income countries. Understanding their prevalence at the healthcare level helps plan early diagnosis, treatment, and prevention strategies. To determine the epidemiological, clinical pattern of sexually transmitted infections among patients attending the Dermatology and Venereology outpatient department of a tertiary care center in the eastern region of Nepal and identify associated demographic and risk factors. Materials and Methods: This was a cross-sectional study of the data obtained from cases of sexually transmitted infections attending the Dermatology and Venereology outpatient of a tertiary care hospital in Biratnagar from 1st April 2024 to 30th March 2025. The demographic details, clinical diagnosis and investigation findings were recorded and analyzed using SPSS 27. Routine laboratory investigations along with sexually transmitted infections workup was done. All the patients visiting dermatology outpatients, with complains of sexually transmitted infections were included in our study. Results: The age of presentations ranged from 18 years to 77 years. Maximum number of cases (n=170, 47%) were in the age group of 21 to 30 years.233 (64.72%) were males and 127(35.2%) were females. Syphilis was the most common diagnosis (n=193, 53.6%). Herpes genitalis (n=60, 16.7%) was the second most common followed by condyloma acuminata (n=55, 15.3%). Foreign workers constituted the largest proportion of participants. Conclusion: Syphilis was the common presentation followed by herpes genitalis and condyloma acuminata. Sexually transmitted infections were common in young age and male sex.